From conflict to crisis : the danger of U.S. actions - Haskin, Jeanne M., 1964- (Algora Publishing, 2012)
A society that is reared on competition will face unsettling challenges to authority if it doesn't set certain functions outside the arena of battle, via systematic enrichment of the affluent minority that has always had the power to topple and ruin the system. Today's preoccupation with America's revolutionary history is not just a piece of theater. At the heart of America's outrage is an inability to lash out and demand redemption from the source of its distress because the pain is inflicted, not by hatred, but by the fundamental lack of stability built into our way of life. Now that a fifth.